EXPERIMENTAL STUDY AND PERFORMANCE OF STRENGTH PROPERTIES OF CALCINED KAOLIN AND SILICA FUME PARENTAGE ADDITION - Elahi, Kamar; Gupta, Harsh (International Journal of Research -GRANTHAALAYAH, 2021)
The article is presenting the various type of strength like as compressive and tensile strength during the time of 7 and 28 days. The specimen ore making as 15cm X 15cm X 15cm size for the testing purpose which is depending on the aggregate size. The results are show that strength performances of concrete with durability aspect are improved using Silica fume parentage addition.